Financial Intermediation and the Costs of Trading in an Opaque Market - Green, Richard C.; Hollifield, Burton; Schürhoff, Norman (Review of Financial Studies, 2007)
Municipal bonds trade in opaque, decentralized broker-dealer markets in which price information is costly to gather. We analyze a database of trades between broker-dealers and customers in municipal bonds. These data were only released to the public with a lag; the market was opaque. Dealers earn lower average markups on larger trades, even though dealers bear a higher risk of losses with larger trades. We estimate a bargaining model and compute measures of dealer?s bargaining power. Dealers exercise substantial market power. Our measures of market power decrease in trade size and increase in the complexity of the trade for the dealer.